2013
DOI: 10.1007/s00424-013-1354-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A potentiates TNFα-induced secretion from human endothelial cells and alters barrier functions controlling neutrophils rights of passage

Abstract: Interleukin-17A (IL-17A) is an important pro-inflammatory cytokine that regulates leukocyte mobilization and recruitment. To better understand how IL-17A controls leukocyte trafficking across capillaries in the peripheral blood circulation, we used primary human dermal microvascular endothelial cells (HDMEC) to investigate their secretory potential and barrier function when activated with IL-17A and TNFα. Activation by TNFα and IL-17A causes phosphorylation of p38 as well as IκBα whereby NFκB subsequently beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
4
22
0
Order By: Relevance
“…As shown in Fig 1A, Western blotting analysis confirmed the previously reported expression of IL-17 (IL-17RA) and IL-36 (IL-1Rrp2) receptor subunits in HDMECs (Fig. 1A) [11,14]. Densitometric analysis (not shown) indicated that IL-17RA and IL-1Rrp2 expression was not significantly influenced by treatment with IL-17A and IL-36γ, alone or in combination with TNF-α (Fig.1A).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in Fig 1A, Western blotting analysis confirmed the previously reported expression of IL-17 (IL-17RA) and IL-36 (IL-1Rrp2) receptor subunits in HDMECs (Fig. 1A) [11,14]. Densitometric analysis (not shown) indicated that IL-17RA and IL-1Rrp2 expression was not significantly influenced by treatment with IL-17A and IL-36γ, alone or in combination with TNF-α (Fig.1A).…”
Section: Resultssupporting
confidence: 87%
“…In the case of tumor necrosis factor (TNF)-α, IL-17A stabilizes the mRNA of TNF-activated genes leading to a signal amplification [13]. IL-17 and TNF-α synergistically stimulate cytokine expression in human melanocytes and ECs [14,15]. In human dermal microvascular ECs (HDMECs), IL-17A cooperates with TNF-α in the induction of CSF1/G-CSF and CXCL1/GRO-α [14], whereas in brain ECs IL-17A alone stimulates the release of CCL2/MCP-1 and CXCL1/GRO-α [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore widely assumed that IL-17, like IL-1 and TNF, will exert its pro-inflammatory effects through activation of ECs. However, we and others have noted that effects of IL-17 on human ECs appear weak compared to the responses by several other stromal cell types such as fibroblasts, synoviocytes or vascular smooth muscle cells (10-12). The effect of IL-17 on PCs, which are related to but distinct from smooth muscle cells, has not been previously examined.…”
Section: Introductionmentioning
confidence: 69%
“…TH17 cells can release a large amount of IL‐17A to promote G‐CSF and KC secretion, and G‐CSF can mobilize neutrophils from the bone marrow to peripheral blood . KC can induce the chemotaxis of pro‐inflammatory cells in particular neutrophils to the lung, consequently increasing inflammatory monocytes and neutrophils and lymphocytes in the BALF of the mice with AE‐IPF and exacerbating the local inflammatory responses in the lung.…”
Section: Discussionmentioning
confidence: 99%